2014
DOI: 10.7554/elife.03206
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A is a retinol binding protein that transports retinol during bacterial infection

Abstract: Retinol plays a vital role in the immune response to infection, yet proteins that mediate retinol transport during infection have not been identified. Serum amyloid A (SAA) proteins are strongly induced in the liver by systemic infection and in the intestine by bacterial colonization, but their exact functions remain unclear. Here we show that mouse and human SAAs are retinol binding proteins. Mouse and human SAAs bound retinol with nanomolar affinity, were associated with retinol in vivo, and limited the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
152
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(165 citation statements)
references
References 51 publications
12
152
1
Order By: Relevance
“…S1 A and B). This structure differs from globular SAA1 and SAA3 proteins (18,19), which are significantly α-helical and devoid of β-sheet structure (Fig. S3C).…”
Section: Resultsmentioning
confidence: 88%
“…S1 A and B). This structure differs from globular SAA1 and SAA3 proteins (18,19), which are significantly α-helical and devoid of β-sheet structure (Fig. S3C).…”
Section: Resultsmentioning
confidence: 88%
“…A recent study further showed that serum amyloid A binds and transports retinoids, which are induced in response to the infection (Dataset S3). Retinoids promote maturation of immune cells, elicit T H 17 responses, and facilitate the regeneration of damaged epithelial barriers (40,41). Coagulative activities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its putative role in immune response, SAA was proposed to modulate blood coagulation ( 11 ), monocyte and neturophil chemotaxis ( 12 ), and HDL functions in cholesterol transport and metabolism (13)(14)(15)(16). SAA is implicated in retinol transport ( 10 ), and elevated plasma SAA is a cardiovascular risk factor ( 17 ). Many aspects of normal functions of SAA and its pathological deposition in amyloid remain unclear and are intimately linked to HDL metabolism.…”
mentioning
confidence: 99%